2020
DOI: 10.1186/s12902-020-0541-6
|View full text |Cite
|
Sign up to set email alerts
|

Manifestations of left ventricular dysfunction and arrhythmia in patients with chronic hypoparathyroidism and pseudohypoparathyroidism: a preliminary study

Abstract: Background: Cardiac damage triggered by severe hypocalcemia is well known. However, the role of chronic hypoparathyroidism (HP) and pseudohypoparathyroidism (PHP) in cardiac health is still unclear. We investigated the effect of chronic HP and PHP on cardiac structure and conductive function in patients compiling with treatment. Methods: The study included 18 patients with HP and eight with PHP aged 45.4 ± 15.4 and 22.1 ± 6.4 years, respectively with a previously regular follow-up. In addition, 26 age-and sex-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…The cardiac manifestation of chronic hypoparathyroidism, with hypocalcemia, is an associated cardiomyopathy with reduced myocardial tension, cardiac cavity enlargement, arrhythmia, and congestive heart failure [6] , [7] , [8] . Hypoparathyroid cardiomyopathy is probably caused by other factors different from the low PTH state, such as an elevated calcium phosphate product, chronic hyperphosphatemia, and elevated levels of Fibroblast growth factor-23 (FGF-23).…”
Section: Discussionmentioning
confidence: 99%
“…The cardiac manifestation of chronic hypoparathyroidism, with hypocalcemia, is an associated cardiomyopathy with reduced myocardial tension, cardiac cavity enlargement, arrhythmia, and congestive heart failure [6] , [7] , [8] . Hypoparathyroid cardiomyopathy is probably caused by other factors different from the low PTH state, such as an elevated calcium phosphate product, chronic hyperphosphatemia, and elevated levels of Fibroblast growth factor-23 (FGF-23).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, other studies reported mixed results. A study from China comparing patients with hypoparathyroidism ( n = 18) with healthy age- and sex-matched controls reported differences in corrected QT interval and mild arrhythmias but no differences in cardiac structure, systolic function, or major cardiac events [ 40 ]. Two separate studies from Denmark reported that patients with postsurgical chronic hypoparathyroidism ( N = 688) did not exhibit increased risk for cardiovascular disease [ 41 ], while cardiovascular disease risk was increased in nonsurgical hypoparathyroidism patients ( N = 180) [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…18 Prolonged hypoparathyroidism can result in LV dysfunction and arrhythmia. 19 LV systolic dysfunction caused by hypoparathyroidism can result in a reversible DCM. 11 Moreover, a rare condition known as chronic hypoparathyroidism-associated cardiomyopathy may result in decreased myocardial tension, expansion of the ventricular cavity, arrhythmia, and congestive heart failure.…”
Section: Diagnosismentioning
confidence: 99%
“…It is linked to calcifications in the brain 18 . Prolonged hypoparathyroidism can result in LV dysfunction and arrhythmia 19 . LV systolic dysfunction caused by hypoparathyroidism can result in a reversible DCM 11 .…”
Section: Dcm Presentation In Hypoparathyroidismmentioning
confidence: 99%